Positive Impact of Aachar-Rasayana on Health - Sunita Pandey; Prabhat Kr Dwivedi; Rohit Ranjan; Pallavi Bharti (International Journal of Ayurveda and Pharma Research, 2022)
The first and foremost aim of Ayurveda - “Swasthasya Swasthya Rakshanam Aaturasya Vikara Prashamanam Cha” is to maintain a healthy state of life and to remain free from the burden of diseases and sufferings so as to accomplish the ultimate goal of human life. To achieve this objective, Ayurveda has advocated certain percepts and rules which can ensure the normal functioning of human body without any hindrance. Ayurveda has suggested schedules of Swasthvritta including Dincharya, Ratricharya, Ritucharya, Rasayana, and Sadvritta as some of the practices and methods that leads to a happy, healthy and long life. In Ayurveda general principles to prevent psychic disturbances, practices preventing psychosomatic disturbances, practices regarding codes of general ethics in diet, behaviour, study, self-control etc. are explained as parts of Sadvritta. True efforts made for the observation of these schedules and conduct give rise to the effects of rejuvenation therapy called Aachar Rasayana that promotes longevity without any attack of diseases. Rasayana is one of the comprehensive disciplines of Ayurveda, which comprises a specialized use of herbs, herbo-mineral formulations, food articles and lifestyle along with self-discipline with social etiquette to achieve the optimum state of tissues that there is least effect of etiological factors on body. A careful analysis of qualities of Aachar Rasayana reveals that most of them are related to Mana, Dhi, Dhriti, along with good conduct. It inculcates the discipline related to mind, character, social, religious and personal life, so as to accord with the happiness and good of the individual and the society as a whole.